Pemanfaatan Aplikasi Digital dalam Mencegah Depresi Postpartum: Literature Review - Sukmawati, Setiani Trie; Anshori, Rika Oktaviani; Pinem, Lina Herida; Wardhani, Mayang Annasya Kusuma; Mega, Mega; Safitri, Mia Zulfa; Pratama, Putri Wilda Yana; Sholeha, Wildatus (Jurnal Kesehatan Holistic, 2021)
Postpartum is a time when many changes in women after childbirth, both physiological, psychological, and sociocultural and spiritual changes take place. Complex physical and emotional changes require adaptation to the life pattern following the labor process and the new role of the woman becoming a mother. Social support and communication are needed to prevent depression, doe to various changes after childbirth. The use of digital applications is a media that can increase support,communication between fellow members to share experiences. Studies have proved that digital applications can prevent depression from occurring in the past teachers. This Study aim to view the effectiveness of digital use of apps in preventing postpartum depression. The authors conducted a simple literacy study of 10 articles on the digital adoption of postpartum depression in 2015-2020. The result obtained are: digital applications are able to assist mother in getting access to timely information, can provide convenience in finding information, helps mothers access information on time, may be helpful in locating information, and it helps to prevent postpartum depression. Based on these findings, digital applications are needed to be devolved in nursing services to facilitate communication and education to the community, especially postpartum mothers to prevent depression postpartum